Handbook on the changing geographies of the state: new spaces of geopolitics - Moisio, Sami; Koch, Natalie; Jonas, Andrew E. G.; Lizotte, Christopher; Luukkonen, Juho (Edward Elgar Publishing, 2020)
This authoritative Handbook presents a comprehensive analysis of the spatial transformation of the state; a pivotal process of globalization. It explores the state as an ongoing project that is always changing, illuminating the new spaces of geopolitics that arise from these political, social, cultural, and environmental negotiations.
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung; Globalisierung; Transformation; Nationalstaat